La adquisición de la asimilación de sonoridad - Bárkányi, Zsuzsanna (Acta Hispanica, 2012)
In the present article we mil display the results of a pilot study on the acquisition of the Spanish laryngeal system by advanced U2 learners. The study contributes to our knowledge about phonological transfer between T1 and L2, in this particular case the acquisition of the voicing properties of Spanish and voicing assimilation in Spanish by native speakers ofHungarian.